2012
DOI: 10.1371/journal.pone.0036702
|View full text |Cite
|
Sign up to set email alerts
|

14-3-3ε Is Required for Germ Cell Migration in Drosophila

Abstract: Although 14-3-3 proteins participate in multiple biological processes, isoform-specific specialized functions, as well as functional redundancy are emerging with tissue and developmental stage-specificity. Accordingly, the two 14-3-3ε proteins in Drosophila exhibit functional specificity and redundancy. Homozygotes for loss of function alleles of D14-3-3ε contain significantly fewer germ line cells (pole cells) in their gonads, a phenotype not shared by mutants in the other 14-3-3 gene leo. We show that althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…D14-3-3ε is present in all Drosophila developmental stages and tissues tested [17], [25] and at least for the gonads, it is co-expressed with DmTTLL3A [35], [36]. At least DmTTLL3A should be co-expressed with 6xHis-g14-3-3 under the ubiquitous TubGal4 driver [36]. It is likely then that the sequence recognized on g14-3-3 and D14-3-3ε by gTTLL3 is not a polyglycylation site for the Drosophila enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…D14-3-3ε is present in all Drosophila developmental stages and tissues tested [17], [25] and at least for the gonads, it is co-expressed with DmTTLL3A [35], [36]. At least DmTTLL3A should be co-expressed with 6xHis-g14-3-3 under the ubiquitous TubGal4 driver [36]. It is likely then that the sequence recognized on g14-3-3 and D14-3-3ε by gTTLL3 is not a polyglycylation site for the Drosophila enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Germ cell transcription, including that of the Trl gene, is activated just prior to the start of this stage, and an increase in GAF activity in PGCs at stage 8 has been detected by anti‐GAGA antibodies. The Trl mutant phenotype in this stage is similar to the stat92E, tre‐1, zfh‐1 , and D14‐3‐3ε mutants (Broihier et al ., ; Kunwar et al ., ; Li et al ., ; Tsigkari et al ., ). However, almost all of the described mutant phenotypes result from abnormal expression of the maternal genes.…”
Section: Discussionmentioning
confidence: 97%
“…However, almost all of the described mutant phenotypes result from abnormal expression of the maternal genes. Only in the D14-3-3e mutant it has been shown that embryonic migration depends on both maternal and zygotic expression (Tsigkari et al, 2012). According to modENCODE data, GAGA sites exist in the regulatory regions of the D14-3-3e gene.…”
Section: The Role Of Gaf In Germ Cell Migrationmentioning
confidence: 99%
“…Protein 14-3-3ε has been noticed to be crucial to cellular metabolism by means of molecular crosstalk with ecdysone receptor (EcR) or through direct interaction with metabolic binding partners [17]. The 14-3-3ε isoform is essential for germ cell migration in Drosophila [42]. In addition, this isoform of 14-3-3 antagonizes the transcription factor FoxO to control growth, apoptosis and longevity in Drosophila [43].…”
Section: Isoform-specific Expression and Roles Of 14-3-3 In Drosophilmentioning
confidence: 99%